REFERENSI ENDOFORA ANAFORIS DAN KATAFORIS DALAM NOVEL MERELAKANMU SEUTUHNYA KARYA YUSUF HAMDANI - Mety Agustina (Universitas Sultan Ageng Tirtayasa, 2021)
This research purposed to describe the using of endophora anaphoric and cataphoric in the Merelakanmu Seutuhnya created by Yusuf Hamdhani. Datas came from padan method with the extralingual of Indonesian language. The analyzis showed: (1) the using of endophora anaphoric with the classification, (a) personal of anaphoric endophora, (b) demonstrativa of anaphoric endophor, and (c) comparrative of anaphoric endophora. (2) the using of acataphoric endophora with the classification, (a) personal of cataphoric endophora, (b) demonstrative of cataphoric endophora. Based on the results of the analysis, it was concluded that the use of anaphoric endophore references in the novel Merelakannmu wholly by Yusuf Hamdhani was dominated by anaphorical endophore references on the type of demonstration.